Hubungan Riwayat Pajanan Pestisida Dengan Kejadian Gangguan Fungsi Hati (Studi pada Wanita Usia Subur di Kecamatan Kersana Kabupaten Brebes) - Arum Siwiendrayanti; Suhartono Suhartono; Nur Endah Wahyuningsih (Jurnal Kesehatan Lingkungan Indonesia, 2012)
Background: Women in Kecamatan Kersana Kabupaten Brebes also involved in farming activities using pesticides. Long term of pesticides exposure was able to cause many kinds of health disorder, including liver disfunction. Liver disfunction on women in childbearing-age would make bad impacts not only to themselves but also to their fetus when they were pregnant. Former research indicated that liver disfunction came as a result of pesticides exposure. Health Profiles of Kabupaten Brebes in 2007 and 2008 recorded increasing rate of liver disfunction. The objective of this research was to analize the assossiation between pesticides exposure and liver disfunction on women in childbearing-age at Kecamatan Kersana Kabupaten Brebes. Method : This was an explanatory research with cross sectional approach. This research took sample of 86 women in childbearing-age from four villages which were chosen purposively. Questionare, tool of blood sampling and laboratory testing, and sheet of laboratory result were used as instruments in this research. Data were collected by laboratory testing to blood samples and interviewing childbearing-age women. Result : All childbearing-age women had normal cholinesterase enzyme level, but 50% of them had cholinesterase enzyme below mean level. Envolvement of childbearing-age women in farming activities was 74,4%. Based on cholinesterase enzyme level and envolvement in farming activities, it was concluded that 33 childbearing-age women (38,4%) had pesticides exposure. Occurence of childbearing-age women to have liver disfunction was 23,3%. There was no assossiation between pesticides exposure and liver disfunction on women in childbearing-age (p=0,538). Pesticides exposure, together with other risk factors, also indicated no assossiation to liver disfunction on women in childbearing-age at Kecamatan Kersana Kabupaten Brebes (p=0,651). Keywords : women in childbearing-age, pesticides exposure, liver disfunction